1996
DOI: 10.3382/ps.0751373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gonadal Steroids and Their Antagonists on the Humoral Immune Response of Immune-Selected Broiler Chicks

Abstract: The effects of gonadal hormones, testosterone (Te) and estrogen (E2) as factors in the development of the immune system in two lines, high response (HC) and low response (LC), of broiler chickens divergently selected for early or late immune maturation were studied. For this purpose, plasma Te and E2 levels were tested and correlated with immune response. Also, the effects of exogenous administration of gonadal steroids testosterone propionate (TP), dihydrotestosterone (DHT), and estradiol 3-benzoate (EB), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 42 publications
4
12
0
Order By: Relevance
“…It can be argued that replication is required before any firm conclusions can be drawn. It is therefore important to note that similar results were obtained in lines of broiler chicks divergently selected on their response to E. coli (43). These results were discussed in a different context, and data were collected on chicks up to 30 days old (long before they are sexually active), but also in this experiment high-response chicks had smaller combs and lower testosterone levels than low-response chicks.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It can be argued that replication is required before any firm conclusions can be drawn. It is therefore important to note that similar results were obtained in lines of broiler chicks divergently selected on their response to E. coli (43). These results were discussed in a different context, and data were collected on chicks up to 30 days old (long before they are sexually active), but also in this experiment high-response chicks had smaller combs and lower testosterone levels than low-response chicks.…”
Section: Discussionsupporting
confidence: 57%
“…2) is in accordance with this assumption. However, this assumption was largely based on mammalian studies (7), and several recent studies in different bird species failed to find an immunosuppressive effect of exogenously administrated testosterone (11,12,43). Furthermore, parasite prevalence does not differ between male and female birds (49), while males typically have higher testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, elevated testosterone can also result in increased levels of corticosterone (Casto et al 2001;Ketterson et al 1991;Klukowski et al 1997;Schoech et al 1999), which may directly suppress immune function (Roberts et al 2009). Similarly, the aromatization of testosterone to estradiol could be the cause of the immunosuppression observed here (Leitner et al 1996;Owen-Ashley et al 2004). The agent directly involved in immunosuppression deserves further study; however, we can say that stimulation of the HPG axis with a hypothalamic releasing hormone eVectively changes immune function.…”
Section: Discussionmentioning
confidence: 85%
“…Severe atrophy of the bursa and an increase in plasma cell population in the oviduct have been observed in DEStreated chickens (Khan et al, 1997). It has also been reported that oestrogen increases the plasma concentration of Ig in broiler chicks (Leitner et al, 1996), and causes an increase in Ig-containing cells in the oviduct, whereas progesterone does not show such effects (Zheng et al, 1997). Studies in mice showed that oestrogen enhanced B-cell maturation and increased antibody production (Wira and Sandoe, 1980;Paavonen et al, 1981 (1997) reported that the population of Ig-containing cells in laying hens and immature hens treated with DES was higher at the two ends of the oviduct.…”
Section: Introductionmentioning
confidence: 88%